Ventilation-Associated Pneumonia in Pediatric Intensive Care in Saudi Arabia: A Two-Year Retrospective Study of Incidence, Risk Factors, and Outcome - Al-Sofyani, Khouloud Abdulrhman (Journal of Pediatric Infectious Diseases, 2023)
Objective This article assesses the incidence, risk factors, and outcomes of ventilator-associated pneumonia (VAP) in pediatric intensive care unit (PICU) patients in western Saudi Arabia.Methods A retrospective cohort study enrolled 375 children admitted to the PICU of King Abdulaziz University Hospital, Jeddah, Saudi Arabia. The study data involves clinical assessment of pediatric patients admitted to the PICU who received mechanical ventilation for ≥ 48 hours to monitor the primary outcome of developing VAP. Statistical analysis with univariate and multivariate analysis, a chi-square test, and a logistic regression model were used to analyze the risk factors associated with VAP.Results The VAP incidence among 375 enrolled patients was estimated to be 29.1% (95% class interval = 24.5–34.0%), accounting for 73.6 cases per 1,000 ventilator days. An approximately 1.4-fold increased mortality risk was observed in VAP cases with no statistical significance (p = 0.248). VAP incidence was independently associated with age groups 0 to 30 days (odds ratio [OR] = 6.88, p = 0.001), 1 to 12 months (OR = 4.55, p = 0.003), and > 6 years (OR = 3.45, p = 0.038), in addition to the nasogastric tube (OR = 2.23, p = 0.019), bronchoscopy (OR = 6.28, p = 0.001), and longer ICU stay including 4 to 7 days (OR = 4.08, p = 0.002) and > 7 days (OR = 4.96, p = 0.002).Conclusion Given the observed high incidence of VAP, it is imperative to urgently enhance our preventive strategies and rigorously scrutinize VAP risk factors within the institution. Extra precautions and specific risk identification may be warranted in high-risk age groups. Our findings underscore the necessity for a comprehensive assessment of risk factors and etiological agents, aligning them with incidence rates. This proactive approach would facilitate the early implementation of strategic interventions and practices, potentially reducing VAP development.
Keywords: ventilator-associated pneumonia; pediatric intensive care unit; incidence; risk factors